2009
DOI: 10.1097/bpb.0b013e32832989be
|View full text |Cite
|
Sign up to set email alerts
|

Scapulothoracic dissociation secondary to major shoulder trauma

Abstract: Three skeletally immature patients with scapulothoracic dissociation were reviewed. A 5-year-old child's arm, caught in a conveyor belt, led to complete upper extremity amputation. Multiple fractures, muscular damage, and cutaneous and subcutaneous tissue disruption (degloving) were present throughout the avulsed extremity. Replantation was considered, but not carried out because of these extensive injuries. He was treated with a myoelectric prosthesis. Two older boys had scapulothoracic dissociation (one open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A retrospective research with 25 STD patients indicated that more than half occurred as a result of a motorcycle accident [Zelle 2004], as well as in our case. Although most patients were adults, a few immature patients with STD also recently have been reported [Lovejoy 2009].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective research with 25 STD patients indicated that more than half occurred as a result of a motorcycle accident [Zelle 2004], as well as in our case. Although most patients were adults, a few immature patients with STD also recently have been reported [Lovejoy 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Combined injuries to neurovascular structures around the shoulder typically result from high-energy trauma as seen in scapulothoracic dissociation (SD), which is characterized as a complete disruption of the scapulothoracic articulation with lateral scapular displacement and intact skin leading to a spectrum of musculoskeletal, neurologic, and vascular injuries 10,23 . SD is a rare traumatic injury most commonly found in adults, with only a few reports in the pediatric age group [24][25][26][27] . In the case reported here, our initial clinical impression was that the patient experienced a subtype of SD, as suggested radiographically by the combined neurovascular injury and laterally displaced scapula.…”
Section: Discussionmentioning
confidence: 99%